PENGARUH MEDIA PEMBELAJARAN UNTAMATIK (UNO STACKO MATEMATIKA MENARIK) TERHADAP HASIL BELAJAR SISWA SD NEGERI 24 TANJUNG BATU - Umi Maulidia; Misdalina; Melinda Puspita Sari Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of the problem in this study is the lack of learning outcomes in mathematics education caused by the application of mathematical media without the assistance of other media. This study aims to determine the effect of the learning media UNTAMATIK (Uno Stacko Matematika Menarik) on the learning outcomes of students at SD Negeri 24 Tanjung Batu. The research method used is an experimental method with a Posttest Only Control Group Design. The subjects of this study are students of class IV A and IV B at SD Negeri 24 Tanjung Batu, totaling 53 students. Data collection methods use tests and documentation. The test instrument consists of multiple-choice questions totaling 10 questions to measure student learning outcomes. The data analysis technique uses Independent Sample T-test. The research results indicate that there is an influence of UNTAMATIK media on the learning outcomes of elementary school students in mathematics, as can be seen from the hypothesis testing results (Independent Sample T-Test) showing a significance value of this study of 0.000 > 0.05, which means Ho is rejected and Ha is accepted.